Gestão de projetos como articulação entre o pedagógico e o administrativo à serviço da missão educativa - Argollo, Juliana Rocha de (Universidade do Vale do Rio dos Sinos, 2024)
This dissertation is the result of an investigation into the contribution of Project Management as a tool for articulating strategic decisions, both in the pedagogical and administrative spheres, through participatory management, in the context of a basic education school. The research was developed at Colégio Antônio Vieira, in a school belonging to the Jesuit Education Network (RJE), an educational institution anchored in the fundamental concepts of Project Management. Bearing in mind this vision focused on this type of management and seeking an improvement in the pedagogical-administrative interrelationship, this research had the general objective of demonstrating how Project Management can be used as a tool for articulating strategic decisions, in the pedagogical and administrative scope, through participatory management. To this end, it was a single case study, adopting a qualitative methodology of a descriptive nature. Thus, the benefits of participatory management and its possible impacts on the implementation of Project Management were highlighted, analyzing the main existing project management models, resulting in the proposal to institutionalize Project Management through the creation of a Permanent Management Committee of Projects and a project matrix to evaluate strategic initiatives. The results indicated that the adoption of these practices can minimize risks, maximize results and promote continuous improvements in the institution, aligning with the strategic objectives and guiding documents of the Jesuit Education Network. Based on these analyses, a viable Intervention Plan was drawn up, which paves the way for new studies that can evaluate how to propose the implementation of project management for strategic decisions in RJE schools and, perhaps, in other educational institutions.
Keywords: Gestão de projetos; Gestão educacional; Gestão participativa; Project management; Educational management; Participative management; ACCNPQ::Ciências Humanas::Educação